The Impact Of Social Media On Microgreens Product Knowledge And Purchase Intention - Muftiyatunnisa, Salmaa; Darsono, Darsono; Anantanyu, Sapja (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose- The purpose of this research is to find out the impact of social media Instagram on microgreens’ product knowledge and purchase intention by using several components of the AISAS model.Design/Methodology- Respondents in this study were 15 to 45 years old and were followers of Instagram accounts that disseminate knowledge and market microgreens’ products. This study uses a simple random sampling method. This study employs a variance-based structural equation modeling (SEM) analysis, that is partial least squares (PLS). The data from this research were analyzed using SmartPLS 3.0 software.Findings- The results revealed that social media significantly affected attention, Interest, and Search. Search has a significant and positive impact on increasing knowledge of microgreens products. Knowledge of microgreens products has a significant impact on purchase intentions of microgreens products. Originality- This research produces new findings regarding consumer behavior on microgreens and their influencing factors. Practical Implications- The results of this study can be used as a reference to find marketing methods and develop the most effective strategies to attract microgreens consumers.